Capture or kill ebook - Flynn, Vince (Mitch Rapp, 2024)
Mitch Rapp faces an Iranian foe bent on destabilizing the Middle East in this "bloody, electrifying adventure" ( The Real Book Spy ) from Vince Flynn's #1 New York Times bestselling series, now written by the "worthy successor to Tom Clancy" ( Publishers Weekly ) Don Bentley. April 2011: On a remote mountaintop overlooking the remains of the Iranian nuclear weapons program, Azad Ashani witnesses the successful demonstration of a new weapons system meant to upend the American-led war in Afghanistan. Ashani, director of the Iranian Ministry of Intelligence and Security and Irene Kennedy's former back channel to the Iranian government, recognizes the demonstration's true significance, and the nation-ending conflict it will provoke. Alone, Ashani stands no chance of preventing this rush to madness. But with the help of one man, he just might. In Washington, DC, CIA director Irene Kennedy briefs the president that the operational window to kill or capture Osama bin Laden at his recently discovered compound in Abbottabad, Pakistan is rapidly closing. But before he'll authorize a commando raid on Pakistani soil, the president demands irrefutable proof of bin Laden's presence. Proof he trusts just one man to provide. Preventing a looming war in the Middle East while delivering justice for the nearly 3,000 Americans killed on 9/11 would be a big ask for anyone but Mitch Rapp isn't just anyone in this high-octane thriller that is perfect for "action junkies" ( Kirkus Reviews ).